Unions and Temporary Help Agency Employment - Bartkiw, Timothy (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2012)
Temporary help agency employment (THAE) is a peculiar and often precarious employment form that has become increasingly salient in Canada in recent decades. Seeking to advance both the literatures on precarious work and union renewal, this article examines the effects of the expansion of this unique employment form upon labour unions, and union responses to this phenomenon.The study employed a qualitative exploratory method, involving twenty-four interviews with key informants from fourteen large labour unions, two union federations, and the Toronto-based workers’ centre known as the “Workers’ Action Centre.” Various effects of the expansion of THAE on unions were identified and categorized as relating to either union organizing or representation activities, and a range of union responses to the phenomenon are also discussed.Overall, it is suggested that THAE growth carries the potential to constrain organizing and representation activities in multiple ways, although its effects are highly mediated by other contextual factors. Union responses have thus far been largely limited to incremental adjustments aimed at shoring up traditional organizing and collective bargaining practices.